Dampak Penutupan Selat Hormuz 2026 terhadap Keamanan Pasokan Minyak di Kawasan Timur Tengah - Deni Hermawan; Ismah Khodimatus Sholihah; Ujang Muhram; Septianis Afipah (Jurnal Sosial Humaniora dan Pendidikan, 2026)
The Strait of Hormuz is the world’s most critical energy chokepoint, with approximately 20–27 percent of global seaborne oil trade passing through it daily. The escalation of conflict between the United States, Israel, and Iran beginning on February 28, 2026, through Operation Epic Fury triggered Iran’s actual closure of the Strait of Hormuz on March 4, 2026, making it the largest energy supply disruption in the history of the global oil market. While previous studies have addressed the risk of Strait of Hormuz closure hypothetically, no research has specifically analyzed the actual impact of the 2026 closure on oil supply security within the Middle East region. This study aims to analyze how the 2026 Strait of Hormuz closure has impacted oil supply security among producing countries in the Middle East, particularly Saudi Arabia, Kuwait, Iraq, and Qatar, using Kenneth Waltz’s Structural Realism perspective. A qualitative descriptive method was employed through literature review and document analysis. The findings indicate that the 2026 closure caused regional oil exports to decline by up to 10 million barrels per day, oil prices surging beyond 100 USD per barrel, damage to major energy infrastructure, and the exposure of structural vulnerabilities in the region. From the Structural Realism perspective, Iran’s closure is a rational response to the anarchic structure of the international system and an effort to preserve its relative power position in global power distribution.